EFFECTS OF AL ON THE MAGNETIC-PROPERTIES OF NANOCRYSTALLINE FE73.5CU1NB3SI13.5B9 ALLOYS - LIM, SH; PI, WK; NOH, TH; KIM, HJ; KANG, IK (AMER INST PHYSICS, 1993)
The effects of Al on the soft magnetic properties of nanocrystalline Fe73.5-xAlxCu1Nb3Si13.5B9 alloy ribbons are investigated in the composition range of 0 less-than-or-equal-to x less-than-or-equal-to 1.0. The relative initial permeability at 1 kHz is found to increase by the addition of Al, and reaches the peak value at x = 0.1. The coercivity decreases, rather significantly, with the Al content in the whole composition range investigated in the present work, the values of the coercivity being 12.5 mOe at x = 0 and 9.3 mOe at x = 1.O. The magnetic induction at an applied field of 10 Oe, however, decreases moderately by the introduction of Al, possibly due to the dilution effect. The improvement in the soft magnetic properties is considered to result from the reduction in the grain size of the alpha Fe-Si solid solution phase of the Al-added alloy ribbons, which has been observed by transmission electron microscopy. Another factor may be due to the decrease in the intrinsic magnetocrystalline anisotropy K1 as Al is added to the alloy.
Keywords: GRAIN-STRUCTURE; FERROMAGNETS